Study of Physical Growth Conformation among Major Thalassemic Children at 5_15 Ages in Babylon Maternity and Children Hospital - doori, Nuhad Al; Al-Musawi, Khatam M.; A. Hassan, Abdul Mahdi (International Journal of Psychosocial Rehabilitation, 2020)
Thalassemia considered one of the most common human inborn illnesses in the world, which causes many problems for the affected children, families and health care system. The objective of the study: is to assess the physical growth configuration of thalassemic children among 5-15 years. Material and method: Descriptive (Non-Probability) design was carried out at child and maternal Babylon hospital-unit of blood diseases. The study was directed through a period extended from (1 May 2018 to end December 2018) on a convenience sample that consists of (150) thalassemic children who had scheduled visits to the center of Thalassemia. Data collection: through a questionnaire constructed for the purpose of the study & filled by the researcher, which consumes up to 25 minutes. It consists of 4 parts including the first three parts related to parental and child’s demographical data while the last part related to such physical growth configuration & medical evaluations. Statistical analysis: through the application of electronic programs SPSS (statistical package for the social sciences) which resulted in the majority of thalassemic child’s weight 39 (26%) with two groups equality (20-24) (25-29) consequently while their height was 57(38%) within (124-135) The most important result was BMI (body mass index) were ranged between (12-14) as 81(54%). The researchers recommend an educational program should be handled on parents concerned certain topics in caring for the thalassemic child particularly the nutrition which has a principal effect on their physical measurements.